Military Sexual Trauma Among Homeless Veterans - Pavao, Joanne (Springer-Verlag, 2013)
BACKGROUND: Military sexual trauma (MST) is the Veteran Health Administration’s (VHA) term for sexual assault and/or sexual harassment that occurs during military service. The experience of MST is associated with a variety of mental health conditions. Preliminary research suggests that MST may be associated with homelessness among female Veterans, although to date MST has not been examined in a national study of both female and male homeless Veterans. OBJECTIVE: To estimate the prevalence of MST, examine the association between MST and mental health conditions, and describe mental health utilization among homeless women and men. DESIGN AND PARTICIPANTS: National, cross-sectional study of 126,598 homeless Veterans who used VHA outpatient care in fiscal year 2010. MAIN MEASURES: All variables were obtained from VHA administrative databases, including MST screening status, ICD-9-CM codes to determine mental health diagnoses, and VHA utilization. KEY RESULTS: Of homeless Veterans in VHA, 39.7 % of females and 3.3 % of males experienced MST. Homeless Veterans who experienced MST demonstrated a significantly higher likelihood of almost all mental health conditions examined as compared to other homeless women and men, including depression, posttraumatic stress disorder, other anxiety disorders, substance use disorders, bipolar disorders, personality disorders, suicide, and, among men only, schizophrenia and psychotic disorders. Nearly all homeless Veterans had at least one mental health visit and Veterans who experienced MST utilized significantly more mental health visits compared to Veterans who did not experience MST. CONCLUSIONS: A substantial proportion of homeless Veterans using VHA services have experienced MST, and those who experienced MST had increased odds of mental health diagnoses. Homeless Veterans who had experienced MST had higher intensity of mental health care utilization and high rates of MST-related mental health care. This study highlights the importance of trauma-informed care among homeless Veterans and the success of VHA homeless programs in providing mental health care to homeless Veterans.